Basinal setting and origin of thick (1·8 km) mass‐flow dominated Grand Conglomérat diamictites, Kamoa, Democratic Republic of Congo: Resolving climate and tectonic controls during Neoproterozoic glaciations. Issue 2 (19th August 2018) - Kennedy, Kirsten; Eyles, Nicholas; Broughton, David
Abstract: The Kamoa sub‐basin, in the south‐eastern part of the Democratic Republic of Congo, is a rift basin that hosts a world‐class stratiform copper deposit at the base of a very thick (1·8 km) succession of matrix‐supported conglomerates (diamictite) (Grand Conglomérat Formation) that has been interpreted by some as the product of deposition in the aftermath of a planet‐wide glaciation. Newly available subsurface data consisting of more than 300 km of drill core throws new light on the origin of diamictite and associated facies types, and their tectonic, basinal and palaeoclimatic setting. Initiation of rifting is recorded by a lowermost subaqueous succession of fault‐related mass flow conglomerates and breccias (the 'Poudingue') with interdigitating coeval and succeeding sandstone turbidites (Mwashya Subgroup). Overlying diamictites of the Grand Conglomérat were deposited as subaqueous debrites produced by mixing and homogenization of antecedent breccias and gravel from the Poudingue and Mwashya sediments with basinal muds. Failure of over‐steepened basin margins and debris flow was likely to be triggered by faulting and seismic activity, and was accompanied by syn‐depositional subaqueous basaltic magmatism recorded by peperites and pillow lavas within diamictites. The thickness of diamictites reflects recurring phases of faulting, volcanism and rapid subsidence allowing continued accommodation of rapidly deposited resedimented facies well below wave base. A distal or indirect, glacial influence in the form of rare dropstones and striated clasts is evident, but tectonically‐driven mass flow destroyed any primary record of glacial climate originally present in basin margin sediments. Such basin margin settings were common during Rodinia rifting and their stratigraphy and facies record a dominant tectonic, rather than climatic, control on sedimentation. Deposition occurred on tectonic timescales inconsistent with a Snowball Earth model for Neoproterozoic diamictites involving a direct glacial contribution to deposition.